PEMBERDAYAAN PETANI GULA AREN DI DESA WANGA AMONGENA KECAMATAN MOTOLING TIMUR - PONDAAG, IRA MARIANA; RURU, JOORIE MARHAEN; KOLONDAM, HELLY (Sam Ratulangi University, 2019)
Farmer empowerment is all efforts to improve the ability of farmers to carry out better farmingthrough education and training, counseling and assistance, developing systems and means of marketingagricultural products, consolidation and guarantee of agricultural land area, easy access to knowledge,technology and information, and institutional strengthening of farmers. Farmer Institution is an institutionthat is developed from, by and for farmers to strengthen cooperation in fighting for the interests of farmersin the form of farmer groups and farmer groups combined. Farming community empowerment is the effortsmade in order to improve the agility of the agribusiness community so that they are able to independentlydevelop themselves and do business sustainably. Farmers can be defined as the work of utilizing biologicalresources by humans to produce food, industrial raw materials, or energy sources, as well as to managetheir living environment to meet their daily needs by using traditional and modern equipment. Aren (Arengapinnata Merr) is one type of palm plant potential and can grow well in the tropics, including in Indonesia.In English literature it is called sugar palm, gomuti palm, and palm sugar. Actually the sugar palm plant(Arenga pinnata) has long been known in Indonesia and around the world. Wanga Amongena Village, EastMotoling Subdistrict, Wanga Amongena Village, is seen from natural resources, namely palm sugar whichis one of the people's livelihoods and is one of the potentials of the village that is favored because of themany communities of Wanga Amongena Village who work as palm sugar farmers. The Government ofWanga Amongena Village takes steps so that the income of palm sugar farmers Wanga Amongena Villagecan meet the daily needs of life by providing assistance such as palm sugar farming equipment as well asgovernment steps and community empowerment institutions in stabilizing the selling price of palm sugar,then given training and socialization from community empowerment institutions on how to improve thesmall palm sugar industry so that in the future the community will be able to run palm sugar farming withsatisfying results for them.Keywords: Empowerment, Farmers, Palm Sugar, Training, sosialization